Abundance and mortality of gray whales at Laguna San Ignacio, Mexico, during the 1997-98 El Niño and the 1998-99 La Niña - Stefan Ludwig; Alejandro Gómez-Gallardo U.; Jorge Urbán R. (Geofísica Internacional, 2003)
Abundance of gray whales in Laguna San Ignacio during 1998 and 1999 was obtained during 28 weekly surveys (February 8 to March 28), and mortality records from 1996-99. Single whale numbers were very similar without significant changes from year to year, but for mother-calf pairs the peaks were delayed and significantly lower. The number of dead calves was similar to previous studies, but there were more adult dead whales in 1999 (60%). The minimum calf mortality rates in 1998 and 1999 were higher than in the 1977-82 and 1996-97 seasons. We submit that El Niño and La Niña events had an effect on the mortality and nutrition of whales, as well as on their winter distribution.